A sentiment analysis on online psychiatrist reviews to identify clinical attributes of psychiatrists that shape the therapeutic alliance - Park, Soo Hwan; Cheng, Christopher P.; Buehler, Nicholas J.; Sanford, Timothy; Torrey, William (Frontiers in Psychiatry, 2023)
Background: While online reviews from physician rating websites are increasingly utilized by healthcare providers to better understand patient needs, it remains difficult to objectively identify areas for improvement in providing psychiatric care. Objectives: To quantitatively characterize the sentiment of online written reviews of psychiatrists to determine clinical attributes that can be strengthened to improve psychiatrists’ therapeutic alliance with their patients. Materials and methods: Sentiment scores of 6400 written reviews of 400 U.S-based psychiatrists on a US-based online physician rating website were obtained through a natural-language-processing-based sentiment analysis. Relationships among sentiment scores, average star ratings, and demographics were examined. Linguistic analyses determined words and bigrams that were highly associated with reviews with the most positive and negative sentiment. Findings: Sentiment scores were significantly correlated with average star ratings of the psychiatrists (R=0.737, p<.001). Psychiatrists who were younger (<56 y.o.) and/or practiced in the Northeast had significantly higher average star ratings than those older and/or practicing in the Southwest. Frequency analysis showed that positive reviews most frequently contained ‘time’ (N=1138) and ‘caring’ (N=784) while negative reviews most frequently contained ‘medication’ (N=495) and ‘time’ (N=379). Logistic regression analysis revealed that reviews were more likely to be considered positive when they included ‘great listener’ (OR=16.89) and ‘comfortable’ (OR=10.72) and more likely to be negative when they included ‘meds’ (OR=0.55) and ‘side effect’ (OR=0.59). Conclusion: Psychiatrists who are younger and located in the Northeast receive more positive reviews; there may be potential for demographic bias among patient reviewers. Patients positively rate psychiatrists who make them feel heard and comfortable but negatively rate encounters centered around medications and their side effects. Our study lends quantitative evidence to support the importance of thorough and empathetic communication of psychiatrists in building a strong therapeutic alliance.